Bahasa Rupa Gambar Anak Berkesulitan Belajar dan Relasinya dengan Gambar Seni Rupa Tradisi - Pandanwangi, Ariesa; Pialang, Yasraf Amir; Adisasmito, Nuning Damayanti (PANGGUNG, 2014)
ABSTRACTÃÂ Children with learning disabilities have creative capabilities that sometimes unnoticed by their pa- rents or teachers. Their creative capabilities are usually observed from their drawings, which as creative as the drawings created in traditional arts. The aim of this research is to determine the relationship between drawings from children with learning disabilities compared to the drawings created in traditional arts.The research methods employed is a qualitative descriptions with visual languages approaches. The approaches used are contents of wimba, way of wimba, enlargement and shrinkage. It can be shown that the way of drawing by children with learning disabilities has direct relationship with the traditional arts. The way of wimba of these childrenÃ¢â¬â¢s drawings is having similar characteristics with the way of wimba in traditional arts. ÃÂ This similarity is observed from the unique way of drawing of these children which are figurative objects drawn on a flat sand surface, various backgrounds, various relieves, tranparencies, emphasizing large objects, green colour, and symmetrical compositions. These similarities are constructed because these children do not know about perspective drawing and gravitational principles in the draw- ing, somethings which are also found in traditional art, so that both tend to have similar way of wimba in drawings. The characteristics of drawing by children with learning disabilities can be seen from the way of wimba figures which are schematics, which should already surpassed by children with similar age.ÃÂ Keywords: Children, Drawings, Learning disabilities, Traditional arts, Visual languageÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Anak berkesulitan belajar mempunyai kreativitas yang belum diketahui oleh orang tua bah- kan guru. Kreativitas yang tergali dari gambar yang dihasilkan oleh Anak Berkesulitan Belajar (ABB), sama kreatifnya dengan gambar yang berasal dari seni rupa tradisi. Penelitian ini untuk mengetahui relasi antara gambar ABB dengan gambar seni rupa tradisi. Relasi adalah hal yang membuat adanya keterhubungan antara gambar ABB dengan gambar seni rupa tradisi.Metode penelitian ini adalah deskriptif kualitatif dengan pendekatan bahasa rupa. Bahasa rupa yang dipergunakan adalah isi wimba, cara wimba, diperbesar atau diperkecil. Hasil pene- litian ini diketahui bahwa cara gambar anak memiliki relasi dengan gambar seni rupa tradisi, yaitu cara wimba gambar ABB mempunyai karakteristik kemiripan dengan gambar seni rupa tradisi. Hal tersebut dapat diamati dari cara khas gambar anak yaitu objek figur digambarkan diatas rata tanah, aneka latar, aneka tampak, tembus pandang, objek yang besar dibuat penting, warna hÃÂ³au, komposisi simetris. Kemiripan tersebut karena anak-anak belum mengenal gam- bar perspektif dan gaya gravitasi pada gambar, hal yang sama juga ditemui dalam seni rupa seni tradisi sehingga mereka memiliki kecenderungan penggambaran cara wimba yang mirip. Sedangkan karakteristik gambar ABB dapat dilihat dari cara wimba figur yang menyerupai bagan, padahal untuk anak seusianya anak sudah melampaui bentuk tersebut.ÃÂ Kata kunci: Anak-anak, Bahasa rupa, Berkesulitan Belajar, Gambar, Seni rupa tradisi